Optimization of Cellular ELISA for Assay of Surface Antigens on Human Synoviocytes. (May 1997) - Smith, Donald D.; Cohick, Christopher B.; Lindsley, Herbert B.
The cellular enzyme-linked immunosorbent assay (CELISA) permits assay of cell surface antigens on intact fixed cells. Using a monolayer of cells as the solid phase, the CELISA offers an inexpensive alternative to flow cytometry. In addition, this protocol has the decided advantages of miniaturization (small numbers of cells) and ease of replication (the 96-well cluster plate format). In efforts to optimize CELISA for detecting surface antigens on human fibroblastlike synoviocytes, the authors found that cell number, serum proteins, choice of culture plate, pipetting technique and fixatives may all impact the results of the CELISA.